Sanggring Tradition as A Symbol of Religiosity of The Community of Java Indonesia : Regional Cultural Exploratory Studies - Raheni Suhita; Kundharu Saddhono; Sri Hastuti; Nela Rizqiya Fitri (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Sanggring is a food served every 23rd of Ramadan at the Jami' Sunan Dalem Mosque in Gumeno Village, Gresik Regency, as a joint iftar menu. The Sanggring tradition is unique and still exists today. Thus, researchers considered it essential to be studied further. This research focused on three issues, as stated in the problem formulation: The history of the Sanggring tradition in Gumeno Village, the implementation process, and symbols of religiosity, values, and functions. In the present study, researchers employed a qualitative research method. The findings revealed that the tradition of fast-breaking with the Sanggring menu was encouraged by Sunan Dalem's illness while doing da'wah (inviting or calling people to embrace Islam) in Gumeno Village, which was later reinforced by the community's magical experiences and beliefs. In the life of the local community, the Sanggring was initially an expression of gratitude for the recovery of Sunan Dalem. Nowadays, its functions have developed into social, cultural, and political.